The Effectiveness of Using Cube Strategy in Developing Creative Thinking Skills in Geography for Tenth Grade Students in Jordan - Albataineh, Mohammad; Talafha, Hamed (Dirasat: Educational Sciences, 2022)
Objectives: The current study aims to identify the effectiveness of using the cube strategy in developing creative thinking skills in geography for tenth grade students in Jordan. The number of study members was (60) students, who were divided into a control group with (29) students, and an experimental group with (31) students. A unit ‘Contemporary Environmental Problems’ of the aforementioned topic was taught using the cube strategy, and the study adopted a ready-made scale to measure the skills of creative thinking, which is Torrance's verbal image scale. Methods: A quasi-experimental research method was followed, where the quasi-experimental design of each of the experimental group and the control group was used (by a pre-post test). Results: The results of the study indicated the superiority of the cube strategy over the usual method in developing skills in general, fluency skills, flexibility and originality, each separately. This superiority was statistically significant. Conclusions: In light of the results, it was recommended to train those who teach geography to use the cube strategy.